Analisis Pengaruh Gaya Kepemimpinan Transaksional dan Budaya Organisasi terhadap Kinerja Karyawan dengan Motivasi sebagai Variabel Intervening (Studi Empiris pada PT. PLN Persero Area Jember) - Aprilia Ramdhani (Universitas Jember, 2016)
This study investigated the influence of transactional leadership style and organizational culture on employee performance and motivation as an intervening variable. The purpose of research is to find empirical evidence about the relationship between transactional leadership style and organizational culture on performance through motivation. This study uses a random sampling of all employees PT.PLN (Persero) Area Jember by 46 respondents. The data was collected by distributing Questionnare. Data collection questionnaire with a list of questions that was adopted from a previous study. The results include a transactional leadership style is a significant positive effect on employee performance, organizational culture a significant positive effect on employee performance, motivation significant positive effect on employee performance, transactional leadership style significant positive effect on motivation, organizational culture significant positive effect on motivation. Keywords: transactional leadership style, organizational culture, motivation, employee performance